Commercial banks and the creditworthiness of less developed countries - Euh, Yoon-Dae (Ann Arbor, Mi. : UMI Research Press, 1979)
The purpose of this study is to identify the determinants of the country's creditworthiness. It presents a normative conceptual framework for creditworthiness within which relevant data and forecast can be conveniently analyzed, and attempts to empirically validate the framework.
Includes index.
Bibliography: p. [99]-104.
osc 14/8/17
Loans
Keywords: Loans, Foreign; Debts, External; Banks and Banking